2004
DOI: 10.1007/s00198-003-1572-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence supporting a role of glucocorticoids in short-term bone loss in burned children

Abstract: Children burned > or =40% total body surface area suffer acute bone loss. The reason(s) for this is uncertain. In order to determine whether high endogenous glucocorticoid production can contribute to the bone loss, we sequentially studied a total of 14 pediatric burn patients for bone histomorphometry; 7 of these patients and 4 controls were studied for characteristics of corticosteroid-induced bone loss, including decreased osteoblasts and down-regulation of the glucocorticoid receptor in bone. We then studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 14 publications
2
53
0
Order By: Relevance
“…The exact cause of the hypermetabolic response is still inadequately understood and the biochemical pathways poorly defined. We know that there is a marked increase in stress hormones including glucocorticoids and catecholamines (14,27). This initial increase is due to stimulation of the HPA axis which should, under normal conditions, be controlled via negative feedback by the products of adrenal stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact cause of the hypermetabolic response is still inadequately understood and the biochemical pathways poorly defined. We know that there is a marked increase in stress hormones including glucocorticoids and catecholamines (14,27). This initial increase is due to stimulation of the HPA axis which should, under normal conditions, be controlled via negative feedback by the products of adrenal stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Little is know about the magnitude of the change in hormone production or how and when the levels return to normal. One study involving 14 pediatric patients showed an 8-fold increase in cortisol levels after severe thermal injury and linked this to a marked decrease in type I collagen and bone formation, together with a lack of detectable surface osteoblasts and a reduction in biochemical markers of osteoblast differentiation (14). The purpose of this study was to determine, in a large clinical prospective trial, the acute and long-term pattern of urine cortisol and catecholamine expression in severely burned children.…”
mentioning
confidence: 99%
“…Using labeled tetracycline, they determined bone turnover rates and found that burned patients have almost no bone formation and synthesis. [76][77][78][79][80][81][82] We did not determine bone turnover rates in this study, however, the biochemical markers that we determined indicate that bone metabolism is dysfunctional very early postburn indicating another target for therapeutic intervention. In a recent study, pamidronate 81 was shown to improve bone metabolism during the acute phase and long-term phase postburn.…”
Section: Discussionmentioning
confidence: 97%
“…63,69,[72][73][74][75] Another striking finding was that osteocalcin and parathyroid hormone were drastically decreased immediately after burn and remained decreased during the acute phase postburn. Klein and colleagues [76][77][78][79][80][81][82] published extensively on bone metabolism postburn. They showed that burned children have decreased BMC and BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Imbalances in hormone and vitamin metabolism such as an eightfold increase in glucocorticoids, hypoparathyroidism resulting in urinary calcium wasting, and a persisting vitamin D deficiency are responsible for a reduction in bone mass as well as bone mineral density in these children. [3][4][5][6][7][8][9] The clinical consequences of these alterations are an increased fracture risk, a reduction in growth velocity, and finally, a likely but unproven reduction in peak bone mass. 2 Therapeutic approaches have been shown to attenuate and increase bone mass after burn in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%